Stable isotope geochemistry and microfossil assemblages of carbonate rocks in the ophiolite mélange zone of the Indo–Myanmar orogenic Belt, NE India: Implications on age and depositional environment. Issue 12 (18th July 2022) - Singh, Athokpam Krishnakanta; Guruaribam, Venus; Singh, Yengkhom Raghumani; Singh, Nongmaithem Ibotombi; Singh, Leimapokpam Romendro; Chaubey, Monika; Tewari, Vinod Chandra; Singh, Wangkheimayum Inaocha; Lakhan, Nongmaithem; Devi, Loitongbam Debala; Chanu, Rajkumari Sanalembi
Abstract : A comprehensive data of whole‐rock and stable isotopic geochemistry along with microfossil assemblages of the carbonate rocks of the ophiolite mélange zone of the Indo–Myanmar orogenic Belt (IMOB), north‐east India are discussed, to determine the influence of terrigenous contamination during the formation of these carbonate rocks and also to understand their depositional environment and ages. These carbonate rocks contain a diverse fauna with the dominance of foraminiferal assemblages of planktonic foraminifera ( Globotruncana sp. and Heterohelix sp., etc.) which indicates they were formed during the Santonian to Maastrichtian age. Based on chemical compositions, these carbonate rocks have been identified as limestone (CaO/MgO > 50.1) to slightly dolomitic limestone (9.1 < CaO/MgO < 50.1). Total rare earth element (REE) contents in these carbonates are variable (22.39–146.05 ppm). The Post‐Archean Australian Shale (PAAS)‐normalized REE + Y patterns of these carbonates exhibit seawater‐like REE patterns with LREE depletion and relative HREE enrichment with negative Ce anomalies (Ce/Ce* = 0.32–0.79) and positive Y (4.42–27.81 ppm) and Eu anomalies (Eu/Eu* = 1.11–1.86), suggesting that they were deposited under an oxygenated environment with contamination by hydrothermal activity. They are also depleted in δ 13 C 0 /00 (PDB) (1.02–1.57 0 /00 ) and δ 18 O 0 /00 (PDB) (−6.37 to −9.00%) values which characterize marine precipitates. Eu anomalies and spread in negative δ 18 O 0 /00 (PDB) values to a lesser extent of δ 13 C 0 /00 (PDB) values of these carbonates suggest their formation was altered by diagenesis in the shallow marine environment. Our new whole‐rock and stable isotope geochemical characteristics, in conjunction with microfacies, suggest that the investigated carbonate rocks might have been formed in low‐energy environments, and deposited in neritic to bathyal palaeoenvironments during the Santonian to Maastrichtian interval. Abstract : Bathymetric distribution of benthic and planktonic foraminifera showing the location of present study foraminifera from the carbonate rocks of the ophiolitic mélange zone, Indo‐Myanmar Orogenic Belt (IMOB), NE India